Synthetic peptides as a novel approach for detecting antibodies against sand fly saliva - Sima, Michal; Ferencova, Blanka; Bhattacharyya, Tapan; Miles, Michael A; Litvinov, Sergey V; Hailu, Asrat; Baneth, Gad; Volf, Petr (PLoS neglected tropical diseases, 2019)
BACKGROUND: Hosts repeatedly bitten by sand flies develop antibodies against sand fly saliva and screening of these immunoglobulins can be employed to estimate the risk of Leishmania transmission, to indicate the feeding preferences of sand flies, or to evaluate the effectiveness of vector control campaigns. Previously, antibodies to sand fly saliva were detected using whole salivary gland homogenate (SGH) or recombinant proteins, both of which also have their disadvantages. This is the first study on sand flies where short peptides designed based on salivary antigens were successfully utilized for antibody screening. METHODOLOGY/PRINCIPAL FINDINGS: Specific IgG was studied in hosts naturally exposed to Phlebotomus orientalis, the main vector of Leishmania donovani in East Africa. Four peptides were designed by the commercial program EpiQuest-B, based on the sequences of the two most promising salivary antigens, yellow-related protein and ParSP25-like protein. Short amino acid peptides were synthesised and modified for ELISA experiments. Specific anti-P. orientalis IgG was detected in sera of dogs, goats, and sheep from Ethiopia. The peptide OR24 P2 was shown to be suitable for antibody screening; it correlated positively with SGH and its specificity and sensitivity were comparable or even better than that of previously published recombinant proteins. CONCLUSIONS/SIGNIFICANCE: OR24 P2, the peptide based on salivary antigen of P. orientalis, was shown to be a valuable tool for antibody screening of domestic animals naturally exposed to P. orientalis. We suggest the application of this promising methodology using species-specific short peptides to other sand fly-host combinations.
Keywords: kozy; Immunoglobulin G; Goats; plošný screening; slinné proteiny a peptidy; Antibodies; Mass Screening; Dogs; zvířata; Salivary Proteins and Peptides; psi; Sheep; Sensitivity and Specificity; Ethiopia; ELISA; peptidy; Enzyme-Linked Immunosorbent Assay; Phlebotomus; Etiopie; ovce; imunoglobulin G; Animals; senzitivita a specificita; Peptides; protilátky